A platinum-based catalyst, a method for preparing the same, an anode and an electrochemical device
Patent Information
- Application Number
- CN202410039667.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-01-10
AI Technical Summary
使用氧化铱基和钌基催化剂具有良好的抗CO毒化的性能,但其活性不足难以应用到燃料电池中,因此为了促进燃料电池的实际应用,还需提高铂基催化剂的CO耐受性
[0013] In the platinum-based catalyst of this invention, the surface of the catalyst nanoparticles is coated with a porous structure. This porous structure allows hydrogen molecules to pass through while blocking CO molecules. This platinum-based catalyst can maintain its catalytic activity for hydrogen even in a high CO concentration atmosphere of 1000ppm CO/H2, and the stable operation time of the battery is significantly extended.
Smart Images

Figure CN117855501B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical catalysts, specifically to a platinum-based catalyst, its preparation method, anode, and electrochemical device. Background Technology
[0002] Hydrogen has the advantage of being clean and pollution-free, and fuel cells are a sustainable, efficient, and environmentally friendly energy conversion device that can directly convert hydrogen fuel into electricity. Currently, over 95% of the hydrogen fuel used comes from natural gas reforming, coal-to-hydrogen, and industrial by-products, which have the natural advantage of low cost, but inevitably contain carbon monoxide (CO). For fuel cell anodes, CO concentrations exceeding 0.2 ppm can severely poison the platinum catalyst. Therefore, improving the catalyst's CO tolerance is of great significance for the practical application of fuel cells.
[0003] Currently, there are three types of anti-poisoning catalysts used in anodes: 1) platinum-based alloy catalysts, such as Pt / Mo and Pt / Ru; 2) single-layer or double-layer Pt catalysts coated on metal oxides; and 3) ruthenium-based encapsulated catalysts. CO adsorbs extremely strongly onto noble metal catalysts. In fuel cells, even a fuel concentration of only 0.2 ppm CO can rapidly poison the anode catalyst. This can be addressed by adding a binary alloy catalyst composed of a metal that readily generates hydrogen and oxygen to promote the oxidation and removal of CO at adjacent platinum sites, thereby improving the oxidation capacity for CO and reducing CO poisoning of Pt. Furthermore, introducing a binary metal can also modulate the d-band center of Pt, thereby weakening CO adsorption. On the other hand, CO adsorption can also be weakened by constructing a barrier layer on the catalyst surface.
[0004] Chinese patent CN105009342A prepared Pt / Ta and Pt / Nb alloys using direct chemical deposition; Chinese patent CN101436669A used supercritical carbon dioxide fluid to deposit organometallic compounds onto a conductive support, and further prepared Pt / Ru / C, Pt / Sn / C, Pt / Ni / C, and Pt / Rh / C alloy catalysts through reduction; Chinese patent CN116646546A modified a carbon support, specifically by loading Pt / C onto a sulfur-modified carbon support. Based on previously published patents, anti-poisoning catalysts are mainly platinum-based alloys and carbon-supported modified catalysts, but their anti-poisoning capabilities remain limited. According to the literature Ehteshami S. et al. Electrochimica Acta 2013, 107, 155, existing platinum-based alloy catalysts still cannot meet the requirements for CO poisoning resistance in fuel cells; only 20 ppm of CO in the fuel can cause various platinum-based alloy catalysts to lose more than 50% of their activity within 1 hour. While iridium oxide-based and ruthenium-based catalysts exhibit good resistance to CO poisoning, their insufficient activity limits their application in fuel cells. Therefore, to promote the practical application of fuel cells, it is necessary to improve the CO tolerance of platinum-based catalysts. Current technologies, which address the issue of catalyst poisoning at the anode in atmospheres containing trace amounts of CO leading to voltage loss and inability to guarantee stable operation of platinum-based catalysts in CO atmospheres exceeding 100 ppm, present a pressing technical challenge: how to prepare a platinum-based catalyst with better CO tolerance for use as the anode in electrochemical devices. Summary of the Invention
[0005] Therefore, the present invention provides a platinum-based catalyst and its preparation method, anode, and electrochemical device. When used as the anode of the electrochemical device, the platinum-based catalyst of the present invention can better withstand CO.
[0006] On one hand, the present invention provides a platinum-based catalyst comprising catalyst nanoparticles and a coating layer covering the catalyst nanoparticles; wherein the coating layer has channels that allow hydrogen molecules to pass through while hindering CO molecules from passing through.
[0007] On the other hand, the present invention provides a method for preparing the aforementioned platinum-based catalyst, comprising the following steps:
[0008] (1) The solution of catalyst nanoparticles supported on the support and the coating layer precursor is mixed, the pH is adjusted to alkaline, and then hydrothermal treatment is performed; and
[0009] (2) The solid product obtained from the hydrothermal treatment in step (1) is cleaned and then subjected to high-temperature pyrolysis under a reducing atmosphere to obtain the platinum-based catalyst.
[0010] On the other hand, the present invention provides an anode comprising the aforementioned platinum-based catalyst or a platinum-based catalyst prepared according to the aforementioned method.
[0011] In another aspect, the present invention also provides an electrochemical device, the electrochemical device comprising the aforementioned anode.
[0012] Beneficial effects:
[0013] In the platinum-based catalyst of this invention, the surface of the catalyst nanoparticles is coated with a porous structure. This porous structure allows hydrogen molecules to pass through while blocking CO molecules. This platinum-based catalyst can maintain its catalytic activity for hydrogen even in a high CO concentration atmosphere of 1000ppm CO / H2, and the stable operation time of the battery is significantly extended. Attached Figure Description
[0014] Figure 1 The image shows the stability curves of the catalysts used as anode catalysts in Example 1 and Comparative Experiments A and B at 1000 ppm CO (CO / H2).
[0015] Figure 2 These are the it curves of the working stability test of the catalysts used as anode catalysts in Example 2 and Comparative Experiment A at 1000ppm CO (CO / H2);
[0016] Figure 3 These are the it curves of the working stability test of the catalysts used as anode catalysts in Example 3 and Comparative Experiment A at 1000ppm CO (CO / H2);
[0017] Figure 4 These are the it curves of the working stability test of the catalysts used as anode catalysts in Example 4 and Comparative Experiment A at 1000ppm CO (CO / H2);
[0018] Figure 5 This is a transmission electron microscope (TEM) image of the target catalyst prepared in Comparative Experiment C. Detailed Implementation
[0019] The present application will now be described in further detail with reference to the accompanying drawings and embodiments. Through these descriptions, the features and advantages of the present application will become clearer and more apparent.
[0020] The term “exemplary” as used herein means “serving as an example, embodiment, or illustration.” Any embodiment illustrated herein as “exemplary” is not necessarily to be construed as superior to or better than other embodiments. Although various aspects of embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless specifically indicated otherwise.
[0021] Furthermore, the technical features involved in the different embodiments of this application described below can be combined with each other as long as they do not conflict with each other.
[0022] In a first aspect, the present invention provides a platinum-based catalyst comprising catalyst nanoparticles and a coating layer covering the catalyst nanoparticles; wherein the coating layer has channels that allow hydrogen molecules to pass through while hindering CO molecules from passing through.
[0023] It should be noted that the platinum-based catalyst of this invention improves the tolerance of catalyst nanoparticles to CO by coating the surface of the catalyst nanoparticles with a porous coating layer. Specifically, the platinum-based catalyst of this invention uses catalyst nanoparticles as the core, with a porous coating layer covering the surface of the catalyst nanoparticles. When the platinum-based catalyst is used as an anode in a CO / H2 atmosphere, hydrogen molecules can quickly pass through the pores and the coating layer to contact the catalyst nanoparticles and complete the oxidation reaction at the anode. However, the pores hinder the passage of CO molecules, significantly prolonging the time it takes for CO to pass through the coating layer and contact the catalyst nanoparticles. Therefore, the platinum-based catalyst can maintain its activity for a longer period of time.
[0024] Therefore, the platinum-based catalyst of this invention improves CO tolerance while maintaining the hydrogen oxidation catalytic activity of the catalyst nanoparticles. Compared with commercial platinum / carbon catalysts operating in a CO-containing hydrogen atmosphere, the tested catalyst stability is improved by nearly an order of magnitude. It is speculated that the pores in the coating layer can extend in various directions, but most pores are perpendicular to the surface of the catalyst nanoparticles or form an angle with the surface of the catalyst nanoparticles, with a smaller proportion of pores parallel to the surface of the catalyst nanoparticles.
[0025] In another embodiment of the platinum-based catalyst according to the present invention, the particle size of the catalyst nanoparticles is 2-5 nm; the coating layer is C3N4 and / or carbon, and the thickness is 0.5-1 nm.
[0026] It should be noted that when the coating layer is carbon, it refers to a common carbon layer, whose elemental composition may include C, etc.
[0027] In one embodiment of the platinum-based catalyst according to the present invention, the catalyst nanoparticles are selected from platinum, ruthenium, palladium, iridium, platinum-ruthenium alloy, and platinum-cobalt alloy, preferably platinum-ruthenium alloy.
[0028] It should be noted that the platinum-based catalyst formed by combining platinum-ruthenium alloy as catalyst nanoparticles with a coating layer, when used as an anode catalyst, can maintain its catalytic activity for a longer period of time in an atmosphere with CO / H2 up to 1000ppm. While maintaining better CO tolerance, it also exhibits excellent hydrogen oxidation catalytic activity.
[0029] In one embodiment of the platinum-based catalyst according to the present invention, the platinum-based catalyst is a supported catalyst, wherein the exposed surface of the support also has the coating layer; the support is selected from carbon, TiO2, carbon nanotubes, SiO2 and Al2O3.
[0030] It should be noted that the platinum-based catalyst of the present invention is a supported catalyst, wherein the catalyst nanoparticles are loaded or supported on a support, and the coating layer is wrapped around the catalyst nanoparticles supported on the support, or in other words, wrapped around the support supporting the catalyst nanoparticles. The coating layer is formed on the surface of the catalyst nanoparticles and the exposed surface of the support.
[0031] Secondly, the present invention provides a method for preparing the aforementioned platinum-based catalyst, comprising the following steps:
[0032] (1) The solution of catalyst nanoparticles supported on the support and the coating layer precursor is mixed, the pH is adjusted to alkaline, and then hydrothermal treatment is performed; and
[0033] (2) The solid product obtained from the hydrothermal treatment in step (1) is cleaned and then subjected to high-temperature pyrolysis under a reducing atmosphere to obtain the platinum-based catalyst.
[0034] It should be noted that in step (1), the solution of catalyst nanoparticles supported on the support is mixed with the solution of coating layer precursor. The catalyst nanoparticles supported on the support means that the support carrying the catalyst nanoparticles and the catalyst nanoparticles are mixed together with the solution of coating layer precursor.
[0035] It should be noted that in the preparation method of the present invention, step (1) involves attaching the coating layer precursor to the catalyst nanoparticles supported on the support, and step (2) involves converting the attached coating layer precursor into a coating layer. In step (1), the pH value is adjusted to be alkaline, which can be achieved by adding alkaline solutions such as KOH solution, NaOH solution, or ammonia solution. For example, the pH value can be adjusted to 8-14. Coating layer precursors, such as melamine, easily form cyanuric acid under acidic conditions, thus failing to attach to the catalyst nanoparticles supported on the support. Therefore, by adjusting the pH value to be alkaline, the coating layer precursor can be more firmly and densely attached to the catalyst nanoparticles supported on the support.
[0036] In one embodiment of the method according to the present invention, the hydrothermal treatment in step (1) is carried out in a hydrothermal reactor; the temperature of the hydrothermal treatment is 160-200°C and the time is 20-30h.
[0037] It should be noted that in the preparation method of the present invention, in step (1), the coating layer precursor is attached to the catalyst nanoparticles supported on the support by hydrothermal treatment. By controlling the temperature of the hydrothermal treatment process as described above, the surface of the catalyst nanoparticles and the coating layer precursor are well activated into an activated state. By controlling the time of the hydrothermal treatment as described above, the coating layer precursor is firmly attached to the surface of the catalyst nanoparticles and grows into a complete and dense coating layer precursor film, so that all surfaces of the catalyst nanoparticles can be covered and protected by the coating layer precursor film.
[0038] It should be noted that when the precursor of the coating layer is melamine, by controlling the temperature and time of the hydrothermal treatment process as described above, some of the melamine is converted into cyanuric acid during the hydrothermal treatment process. The remaining melamine and the converted cyanuric acid are compounded in a certain ratio. After the melamine and cyanuric acid undergo high-temperature pyrolysis under the reducing atmosphere in step (2), a coating structure with a strong hydrogen bond network is formed on the surface of the catalyst nanoparticles, namely the above-mentioned coating layer. The coating layer forms channels that allow hydrogen molecules to pass through while blocking CO molecules. When the platinum-based catalyst with such a coating layer is used as an anode catalyst in a hydrogen fuel cell, it can effectively catalyze the oxidation reaction of hydrogen and effectively avoid CO poisoning.
[0039] In another embodiment of the method according to the present invention, the reducing atmosphere in step (2) is an H2 / Ar atmosphere; the high-temperature pyrolysis is carried out at a temperature of 300-600°C, preferably 500-550°C, for 2-6 hours.
[0040] It should be noted that in the preparation method of the present invention, the high-temperature pyrolysis in step (2) under the above-mentioned reducing atmosphere decomposes the coating layer precursor attached to the catalyst nanoparticles into a coating layer composed of C3N4 and / or carbon. In step (2), an H2 / Ar atmosphere is used as the atmosphere for high-temperature pyrolysis, and the temperature and time of high-temperature pyrolysis are controlled as above, so that the coating layer precursor attached to the catalyst nanoparticles is transformed into a coating layer with pores that allow hydrogen molecules to pass through while blocking CO molecules from passing through; specifically, high-temperature pyrolysis is carried out in an H2 / Ar atmosphere, so that the coating layer precursor attached to the catalyst nanoparticles is reduced and decomposed into a coating layer. The atmosphere of high-temperature decomposition contains both H2 and Ar, wherein the volume percentage of H2 can be 5% to 10%. Such a high-temperature pyrolysis atmosphere is beneficial for the coating layer precursor to be transformed into a coating layer. During the layering process, channels that allow hydrogen molecules to pass through while blocking CO molecules are formed. By performing high-temperature pyrolysis at the above-mentioned temperature and time, the coating precursor is completely transformed into the coating layer. In particular, when the high-temperature pyrolysis temperature is controlled at 500-600℃, specifically 550℃, the pores in the formed coating layer have the best CO blocking performance. If the temperature is too high, the pores in the coating layer will be too large to block CO, and the resulting coating layer will have the most channels that allow hydrogen molecules to pass through while blocking CO molecules. The resulting platinum-based catalyst can maintain good hydrogen catalytic activity when used for anodic catalysis and can better tolerate CO.
[0041] In one embodiment of the method according to the present invention, in step (2), the cleaning includes sequentially performing a first solvent cleaning 2 to 5 times, a second solvent cleaning 2 to 5 times, and a water cleaning 2 to 5 times; the first solvent and the second solvent are tetrahydrofuran or isopropanol.
[0042] It should be noted that cleaning with the above solvent according to the above steps can effectively remove organic matter and other impurities from the platinum-based catalyst. In particular, after cleaning, the pores in the coating layer of the resulting platinum-based catalyst allow hydrogen molecules to pass through while hindering CO molecules. Therefore, when the platinum-based catalyst is used for anode catalysis in hydrogen fuel cells, hydrogen can contact the catalyst nanoparticles through the above pores to undergo catalytic oxidation, which can effectively exert the catalytic activity of hydrogen oxidation. At the same time, it can prevent CO from contacting the catalyst nanoparticles through the pores, effectively prolonging the time for the platinum-based catalyst to maintain its activity.
[0043] In one embodiment of the method according to the present invention, the coating layer precursor in step (1) is selected from one or more of melamine, dicyandiamide, urea, oleylamine, polyvinylpyrrolidone, starch and dopamine, preferably melamine.
[0044] It should be noted that by selecting the above-mentioned coating layer precursor, especially melamine, and performing hydrothermal treatment according to the conditions in step (1) of the preparation method of the present invention, and performing high-temperature pyrolysis according to the conditions in step (2), melamine can effectively form a coating layer on the surface of the catalyst nanoparticles that allows hydrogen molecules to pass through while hindering CO molecules from passing through the pores.
[0045] In one embodiment of the method according to the present invention, in step (1), the concentration of the solution of the coating layer precursor is 0.02 to 3 mg / mL;
[0046] The solution of the catalyst nanoparticles supported on the carrier and the coating layer precursor are mixed in the following proportions:
[0047] The ratio of the mass of the catalyst nanoparticles supported on the carrier to the solution volume of the coating layer precursor is 100 mg: (100-150) mL.
[0048] It should be noted that in the ratio of the mass of the catalyst nanoparticles supported on the support to the solution volume of the coating precursor, the mass of the catalyst nanoparticles supported on the support represents the total mass of the catalyst nanoparticles supported on the support. The concentration of the coating precursor solution can also be 0.03 mg / mL, 0.05 mg / mL, 0.08 mg / mL, or 1 mg / mL, etc. The mass percentage of the coating precursor in the noble metal of the catalyst nanoparticles can be 0.5% to 7%, specifically 5%, 6%, 6.25%, 6.5%, etc.
[0049] It should be noted that in the preparation method of the present invention, in step (1), the concentration of the solution of the coating layer precursor is controlled as above, and the solution of the catalyst nanoparticles supported on the support and the coating layer precursor is mixed in the above ratio. Then, after the above hydrothermal treatment and high-temperature pyrolysis, the coating layer precursor is uniformly formed on the surface of the catalyst nanoparticles supported on the support to form a coating layer. In particular, the coating layer can well form pores that allow hydrogen molecules to pass through while blocking CO molecules from passing through.
[0050] Thirdly, the present invention provides an anode comprising a platinum-based catalyst according to each of the foregoing embodiments or a platinum-based catalyst prepared according to the methods of each of the foregoing embodiments.
[0051] It should be noted that the platinum-based catalyst in the anode of this invention can better withstand CO. When the platinum-based catalyst forms an ink with Nafion, solvent, etc., and is then dropped onto a rotating disk electrode as an anode, for example, when used in a three-electrode system for detection, it can maintain stable operation for a longer period of time in a 1000ppm CO / H2 atmosphere.
[0052] Fourthly, the present invention provides an electrochemical device comprising an anode according to the foregoing embodiments.
[0053] It should be noted that the electrochemical device can be a battery, such as a proton exchange membrane fuel cell, a medium-temperature fuel cell, or a hydrogen fuel cell. The anode of the electrochemical device is coated with the platinum-based catalyst of this invention, so it can be directly used for anti-poisoning of seawater by electrolysis, anti-poisoning of phosphoric acid in medium-temperature fuel cells, etc.
[0054] The present invention will be further described in detail below through examples. Unless otherwise specified, all reagents and other items used in the following examples can be commercially available finished products.
[0055] The Pt / Ru / C catalyst used in the following examples was purchased from Shengerno 60% Pt / Ru / C, brand name SPT40RU20; the pH value was adjusted to be alkaline by adding 0.1M KOH solution in the following examples; the Nafion solution used in the following test examples was DuPont Nafion solution D2020.
[0056] Example 1
[0057] Add 250 mL of 0.03 mg / mL melamine aqueous solution to 200 mg Pt / Ru / C in a hydrothermal reactor, adjust the pH to 10, and hydrothermally treat at 180 °C for 24 h. Then centrifuge three times with tetrahydrofuran, three times with isopropanol, and three times with water to obtain a powder precursor. Pyrolyze the powder precursor at 550 °C in an H2 / Ar atmosphere (H2 volume percentage of 5%) for 4 h to obtain the target catalyst.
[0058] Example 2
[0059] Add 250 mL of 0.03 mg / mL oleylamine aqueous solution to 200 mg Pt / Ru / C in a hydrothermal reactor, adjust the pH to 10, and perform hydrothermal treatment at 180 °C for 24 h. Then, centrifuge three times with tetrahydrofuran, three times with isopropanol, and three times with water to obtain a powder precursor. Pyrolyze the powder precursor at 550 °C in an H2 / Ar atmosphere (H2 volume percentage of 5%) for 4 h to obtain the target catalyst.
[0060] Example 3
[0061] Add 250 mL of 0.03 mg / mL polyvinylpyrrolidone (PVP) aqueous solution to 200 mg Pt / Ru / C, then add an appropriate amount of melamine aqueous solution (0.02 mg / mL, 50 mL) to a hydrothermal reactor, adjust the pH to 10, and hydrothermally treat at 180℃ for 24 h. Afterward, centrifuge three times with tetrahydrofuran, three times with isopropanol, and three times with water to obtain a powder precursor. Pyrolyze the powder precursor at 550℃ in an H2 / Ar atmosphere (H2 volume percentage is 5%) for 4 h to obtain the target catalyst.
[0062] Example 4
[0063] Add 250 mL of 0.03 mg / mL starch aqueous solution to 200 mg Pt / Ru / C, then add an appropriate amount of melamine aqueous solution (0.02 mg / mL, 50 mL) to a hydrothermal reactor, adjust the pH to 10, and hydrothermally treat at 180℃ for 24 h. Then centrifuge three times with tetrahydrofuran, three times with isopropanol, and three times with water to obtain a powder precursor. Pyrolyze the powder precursor at 550℃ in an H2 / Ar atmosphere (H2 volume percentage is 5%) for 4 h to obtain the target catalyst.
[0064] Example 5
[0065] Add 250 mL of 0.03 mg / mL urea aqueous solution to 200 mg Pt / Ru / C, then add an appropriate amount of melamine aqueous solution (0.02 mg / mL, 50 mL) to a hydrothermal reactor, adjust the pH to 10, and hydrothermally treat at 180℃ for 24 h. Afterward, centrifuge three times with tetrahydrofuran, three times with isopropanol, and three times with water to obtain a powder precursor. Pyrolyze the powder precursor at 550℃ in an H2 / Ar atmosphere (H2 volume percentage is 5%) for 4 h to obtain the target catalyst.
[0066] Example 6
[0067] Add 250 mL of 0.03 mg / mL dicyandiamide aqueous solution to 200 mg Pt / Ru / C, then add an appropriate amount of melamine aqueous solution (0.02 mg / mL, 50 mL) to a hydrothermal reactor, adjust the pH to 10, and hydrothermally treat at 180℃ for 24 h. Afterward, centrifuge three times with tetrahydrofuran, three times with isopropanol, and three times with water to obtain a powder precursor. Pyrolyze the powder precursor at 550℃ in an H2 / Ar atmosphere (H2 volume percentage is 5%) for 4 h to obtain the target catalyst.
[0068] Example 7
[0069] Add 250 mL of 0.03 mg / mL dopamine aqueous solution to 200 mg Pt / Ru / C, then add an appropriate amount of melamine aqueous solution (0.02 mg / mL, 50 mL) to a hydrothermal reactor, adjust the pH to 10, and hydrothermally treat at 180℃ for 24 h. Then centrifuge three times with tetrahydrofuran, three times with isopropanol, and three times with water to obtain a powder precursor. Pyrolyze the powder precursor at 550℃ in an H2 / Ar atmosphere (H2 volume percentage is 5%) for 4 h to obtain the target catalyst.
[0070] Comparative Experiment A
[0071] A commercial Pt / Ru / C catalyst (HISPEC10000) purchased from Johnson Matthey was used directly as the catalyst.
[0072] Comparative Experiment B
[0073] A commercial Pt / C catalyst (brand name SPT20) purchased from Alfa Aesar was used directly as the catalyst.
[0074] Comparative Experiment C
[0075] The target catalyst was prepared using the platinum-ruthenium black catalyst TEC86E86 purchased from TANAKA, following the method described in Example 1. The prepared target catalyst was characterized by transmission electron microscopy (TEM), and the characterization results are shown below. Figure 5 .pass Figure 5 It can be seen that the platinum-ruthenium catalyst surface is coated with a carbon-nitrogen modification layer, and the morphology and thickness of the coating layer on the surface of the platinum-ruthenium catalyst can be observed. This demonstrates that the method of Example 1 of this application can coat the outer surface of the catalyst with a carbon-nitrogen modification layer or a carbon-nitrogen barrier layer.
[0076] Test Example 1
[0077] The catalysts prepared in Examples 1-4 and the catalysts in Comparative Experiments A-B were respectively formulated into inks for electrochemical testing. The ink composition was: 1 mg of catalyst; 0.01 mL of 20 wt% Nafion solution; and 0.5 mL each of water and isopropanol. The inks were ultrasonically dispersed in an ice-water bath until uniformly dispersed. 10 μL of the prepared ink was uniformly dropped onto the surface of a rotating disk electrode for electrochemical testing.
[0078] Electrochemical testing includes the following steps:
[0079] (1) First, perform cyclic voltammetry scanning on the rotating disk electrode with ink droplets between -0.27 and 0.2V until the curve stabilizes, thus completing the activation;
[0080] (2) In an atmosphere containing 1000 ppm CO (0.1% CO, 99.9% H2, i.e., 1000 ppm CO / H2), the hydrogen oxidation stability test for CO tolerance was conducted with the potential controlled at -0.2 V. The test was carried out in a 0.1 M HClO4 solution, using a saturated calomel electrode as the reference electrode, a carbon rod as the counter electrode, and the aforementioned rotating disk electrode with added ink as the working electrode.
[0081] The stability curves of the catalysts in Example 1 and comparative experiments A and B, after undergoing the above process, in 1000 ppm CO / H2 are shown below. Figure 1 As shown in the figure. The stability test curves of the catalysts in Example 2 and Comparative Experiment A, after the above process, in 1000ppm CO / H2 are shown in the figure. Figure 2 As shown in the figure. The stability test curves of the catalysts in Example 3 and Comparative Experiment A, after the above process, at 1000 ppm CO / H2 are shown in the figure. Figure 3 As shown in the figure. The stability test curves of the catalysts in Example 4 and Comparative Experiment A, after the above process, in 1000ppm CO / H2 are shown in the figure. Figure 4 As shown.
[0082] pass Figures 1-4 It can be seen that the catalysts prepared in Examples 1 to 4, when used as anodes, can maintain stable current for a longer period of time when operating in the above-mentioned atmosphere of 1000 ppm CO. The electrode constructed with the catalyst in Example 1 can operate stably for more than 24 hours in the above-mentioned atmosphere, indicating that the catalyst's tolerance to CO is significantly improved. Therefore, purified reformed gas can be used as fuel, which can significantly reduce voltage consumption and improve test stability.
[0083] Test Example 2
[0084] High-resolution transmission electron microscopy (HRTEM) analysis revealed that the target catalysts prepared in Examples 1-7 have a core-shell structure, with a Pt / Ru / C catalyst as the core and a coating layer surrounding it. HRTEM analysis also showed that the particle size of the Pt / Ru / C catalyst core is 3-5 nm, and the thickness of the coating layer in the target catalysts prepared in Examples 1-7 is 0.5-1 nm. Fourier transform infrared spectroscopy and other methods revealed that the coating layer in the target catalysts prepared in Examples 1, 5, and 6 is C3N4, the coating layer in the target catalysts prepared in Examples 2 and 3 is a carbon layer, and the coating layer in the target catalysts prepared in Examples 4 and 7 is a coating layer containing both C3N4 and carbon.
[0085] The present application has been described above with reference to preferred embodiments; however, these embodiments are merely exemplary and illustrative. Various substitutions and modifications can be made to the present application based on these embodiments, all of which fall within the protection scope of the present application.
Claims
1. A method for preparing a platinum-based catalyst, characterized in that, The platinum-based catalyst comprises catalyst nanoparticles and a coating layer covering the catalyst nanoparticles; wherein the coating layer has channels that allow hydrogen molecules to pass through while blocking CO molecules from passing through, and the thickness of the coating layer is 0.5~1 nm. The catalyst nanoparticles have a particle size of 2-5 nm; the coating layer is C3N4. The catalyst nanoparticles are a platinum-ruthenium alloy; The platinum-based catalyst is a supported catalyst, wherein the exposed surface of the support also has the coating layer; The method for preparing the platinum-based catalyst includes the following steps: (1) The solution of catalyst nanoparticles supported on the support and the coating layer precursor is mixed, the pH value is adjusted to 8-14, and then hydrothermal treatment is performed; and (2) The solid product obtained from the hydrothermal treatment in step (1) is washed and then subjected to high-temperature pyrolysis under a reducing atmosphere to obtain the platinum-based catalyst. In step (1), the hydrothermal treatment is carried out in a hydrothermal reactor; the temperature of the hydrothermal treatment is 160~200℃, and the time is 20~30 h. In step (2), the reducing atmosphere is an H2 / Ar atmosphere; the high-temperature pyrolysis is carried out at a temperature of 300~600℃ for 2~6 h. The coating layer precursor is melamine. In step (1), the concentration of the solution of the coating layer precursor is 0.02 ~ 3 mg / mL; The solution of the catalyst nanoparticles supported on the support and the coating layer precursor are mixed in the following proportions: The ratio of the mass of the catalyst nanoparticles supported on the support to the solution volume of the coating layer precursor is 100 mg: (100~150) mL, wherein the mass of the catalyst nanoparticles supported on the support represents the total mass of the catalyst nanoparticles supported on the support.
2. The method according to claim 1, characterized in that, The support is selected from one of carbon, TiO2, SiO2 and Al2O3.
3. The method according to claim 2, characterized in that, The carrier is a carbon nanotube.
4. The method according to claim 1, characterized in that, The high-temperature pyrolysis is carried out at a temperature of 500~550℃ for 2~6 hours.
5. The method according to claim 1, characterized in that, In step (2), the cleaning includes sequentially performing a first solvent cleaning 2 to 5 times, a second solvent cleaning 2 to 5 times, and a water cleaning 2 to 5 times; The first solvent is tetrahydrofuran, and the second solvent is isopropanol.
6. A platinum-based catalyst prepared by the method according to any one of claims 1-5.
7. An anode of an electrochemical device, characterized in that, The anode of the electrochemical device comprises the platinum-based catalyst prepared by the method according to any one of claims 1 to 5.
8. An electrochemical device, characterized in that, The electrochemical device includes the anode of the electrochemical device according to claim 7.
Citation Information
Patent Citations
Anode CO resistant catalyst for fuel batter with proton exchange film and preparation method thereof
CN101436669A
Use of anode catalyst layer
CN105009342A
Application of sulfur-containing platinum-carbon catalyst in improving CO toxicity resistance of platinum-carbon catalyst
CN116646546A
Synthesis method, product and application of carbon nitride nanotube with cross-linked structure characteristic
CN111634893A
Post-treatment method of carbon-coated catalyst for proton exchange membrane fuel cell
CN115986153A